Virginia Woolf's Jacob's Room: An Introduction and Annotations. - Neverow, Vara (2007)
Keywords: dept.eng; faculty_collection; sabbatical_report

Grace Cavalieri Interviews Vivian Shipley - Cavalieri, Grace; Shipley, Vivian (2007)
Keywords: 21st century; 21st century; Poets, American; American poetry; Interviews; award_winner; dept.eng; faculty_collection

General Ojukwu: The Legend of Biafra - Ogbaa, Kalu (Triatlantic African history-makers series, 2007)
Keywords: 1960-1975; Africa; Africa; Biography; Biography; Nigeria; Biography; Statesmen; Ojukwu, Chukwuemeka Odumegwu, 1933-2011; Politicians; Politics and government; dept.eng; faculty_collection

Reviewers reviewed: John Davis and the early American leterary field - Ellis, S. (Early American Literature, 2007)
Keywords: dept.eng

Opinion: Ethos interrupted: Diffusing "star" pedagogy in creative writing programs - Ritter, K. (College English, 2007)
Keywords: dept.eng; ⛔ No DOI found

Popular millenarianism and empire in Blake's night thoughts - Rosso, G.A. (Blake, Modernity and Popular Culture, 2007)
Keywords: dept.eng

The Emotional Effects of Literacy: Vietnamese Women Negotiating the Shift to a Market Economy - Crawford, I.W. (WOMEN and LITERACY, 2007)
Vietnam's 1986 doi moi reforms are transforming Vietnam from a socialist economy to a socialist market economy. In addition to liberalized laws allowing
Keywords: dept.eng

Emotional Expression in Malory's Elaine of Ascolat - Holbrook, Sue Ellen (Parergon, 2007)
Shrieks and complaints, accompanied by body language, contribute markedly to Malory's representation of Elaine of Ascolat's emotionality. Elaine's two shrieks echo Lancelot's and indicate change from sorrow for a wounded beloved to heartbreak when he rejects her. When Elaine is compared with speakers in love lyrics, allegories, and romances, the thoughts in her unarticulated complaints after the pained second shriek may be understood and related to her defence of complaint and perseverance in love despite rejection. Similarly, Elaine's complaint letter, including its overlooked moan to ladies, reflects a state of tranquility and brings about a just resolution.
Keywords: dept.eng

Ethos interrupted: diffusing "Star" pedagogy in creative writing programs - Ritter, Kelly (College English, 2007)
Keywords: dept.eng